A collection of Book Reviews for Volume 8, Number 1 (Verbum et ecclesia, 1987)
Verbum et Ecclesia is a theological research journal that challenges traditional discourses within and between the fields of biblical, religious, social and human sciences as well as the constructive engagement with the natural sciences. It is an instrument of engagement between theological disciplines, on the one hand, and theology and other disciplines, on the other.